Early career researchers in the pandemic-fashioned ‘new scholarly normality’: a first look into the big changes and long-lasting impacts (international analysis) - Nicholas, David; Herman, Eti; Boukacem-Zeghmouri, Cherifa; Watkinson, Anthony; Sims, David; Rodriguez-Bravo, Blanca; Świgon, Marzena; Abrizah, Abdullah; Xu, Jie; Serbina, Galina; Jamali, Hamid R.; Tenopir, Carol; et al. (El profesional de la información)
After two-years of repeat interviewing around 170 early career science/social science researchers from China, France, Malaysia, Poland, Russia, Spain, UK and US about their work life and scholarly communications in pandemic-times, the Harbingers project is now in possession of a mountain of data on what constitutes a very important academic topic. The purpose of the paper is to share the early highlights of the data, with a focus on the main and lasting impacts of the pandemic. The data presented comes from the national interviewers, who had conducted 3 rounds of interviews with their 20 or so early career researchers (ECRs) over two years and, thus, knew them well. They were asked to provide an ‘aerial view’ by identifying the most important impacts they had detected while things were still fresh in their minds. The main findings are that: 1) ECRs, the research workhorses, have generally proved to be resilient and perseverant and some have prospered; 2) the pandemic has fast-tracked researchers to a virtual and remote scholarly world, with all the advantages and disadvantages that comes with it. The data, however, is nuanced, with significant differences occurring between countries, especially China and France. The paper also updates a literature review on the topic previously published in this journal.